High Serum Anti-Müllerian Hormone Concentrations Are Associated With Poor Pregnancy Outcome in Fresh IVF/ICSI Cycle but Not Cumulative Live Birth Rate in PCOS Patients - Guo, Yaxin; Liu, Shuai; Hu, Shiqiao; Li, Fei; Jin, Lei (Frontiers in Endocrinology, 2021)
Objective: To investigate the association between baseline serum Anti-Müllerian hormone (AMH) levels and IVF/ICSI outcomes in women with polycystic ovary syndrome (PCOS). Design: Retrospective study. Setting: Reproductive medicine center in a hospital. Population: 2436 PCOS patients (Rotterdam criteria) who underwent their first fresh IVF/ICSI cycles were divided into three groups on the basis of the <25th (Group 1, n=611), 25 to 75th (Group 2, n=1216), or >75th (Group 3, n=609) percentile of baseline serum AMH level. Intervention(s): Baseline serum AMH levels measured on the 2-3 days of spontaneous menstrual cycle before IVF/ICSI treatment. Main Outcome Measure(s): Live birth rate (LBR), cumulative live birth rate (CLBR), clinical pregnancy rate (CPR) and normal fertilization rate (FR). Result(s): The LBR, CPR and FR were significantly increased in Group 1 than Group 2 and Group 3, however, CLBR was similar between the three groups. The LBR were 46.6%, 40.5% and 39.4% in Group 1, Group 2 and Group 3 respectively. And the CPR were 53.0%, 47.0%, and 45.5%, respectively. The FR was highest in Group 1 (61.7%, P<0.05), but there was no uniform reverse trend with AMH level. And CLBR were 68.7%, 70.4%, and 71.3%, respectively. Although women in Group 1 were older (p < 0.05) and had higher body mass index (BMI) (p < 0.05), binomial logistic regression analysis used age, BMI, FSH and AMH as independent variables indicated that only AMH was significantly associated with LBR and CPR. Nevertheless, binomial logistic regression analysis used age, BMI, FSH, AMH and number of retrieved oocytes as independent variables indicated that only number of retrieved oocytes was significantly correlated with CLBR. After stratifying by age, the negative relationship between baseline AMH level and LBR and CPR remained only in the patients <30 years old. Conclusion(s): Higher baseline AMH level in PCOS women resulted in lower LBR, CPR and FR but not influence CLBR.